Effects of Catalytic Bed Thermal Characteristics on Liquid Monopropellant Decomposition and Combustion Characteristics within an Eco-Friendly Thruster Based on Ammonium Dinitramide. Issue 6 (2nd June 2016) - Zhang, Tao; Li, Guoxiu; Yu, Yusong; Chen, Jun; Wang, Meng
ABSTRACT: In this article, the effect of catalytic bed thermal characteristics on the combustion processes of ammonium dinitramide (ADN)-based environmentally friendly propellant within the monopropellant thruster are analyzed. The thermal characteristics are described by considering the thruster outer wall radiation, thermal non-equilibrium temperature models, and thermal dispersion effect in the catalytic bed. This is filled with highly effective catalyst particles through the computational fluid dynamic simulation software called ANSYS Fluent. The results of spray hitting the wire mesh are achieved through an experiment, and the process of the liquid propellant evaporation is also considered. Profiles describing thermal characteristics of the catalytic bed by the user-defined function (UDF) are utilized to achieve the heat transfer characteristics by considering the non-equilibrium temperature models with thermal dispersion effect. The P1 radiation model takes into account the influence of the high temperature generated by the decomposition and combustion processes within the ADN thruster. The results demonstrate that the thermal characteristics have significant effects on the decomposition and combustion processes. Meanwhile, the influence of the thermal dispersion effect, decomposition and composition mechanisms, as well as the influence of the methanol mass fraction on the heat transfer are tested to provide an in-depth understanding of the operating mechanism within the ADN thruster.